2019
DOI: 10.1002/jbmr.3704
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal Electromagnetic Fields Increase Peak Bone Mass in Rats by Activating Wnt10b/β-Catenin in Primary Cilia of Osteoblasts

Abstract: Extremely low‐frequency electromagnetic fields have been considered a potential candidate for the prevention and treatment of osteoporosis; however, their action mechanism and optimal magnetic flux density (intensity) parameter are still elusive. The present study found that 50‐Hz sinusoidal electromagnetic fields (SEMFs) at 1.8 mT increased the peak bone mass of young rats by increasing bone formation. Gene array expression studies with femoral bone samples showed that SEMFs increased the expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 50 publications
(110 reference statements)
6
38
1
1
Order By: Relevance
“…Furthermore, animal studies found that EMFs prevented ovariectomy-induced OP, attenuated microgravity-induced bone loss, and increased the peak bone mass in growing young rats (Lei et al, 2018;Li et al, 2018; Y. Y. Zhou et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, animal studies found that EMFs prevented ovariectomy-induced OP, attenuated microgravity-induced bone loss, and increased the peak bone mass in growing young rats (Lei et al, 2018;Li et al, 2018; Y. Y. Zhou et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is still no consensus about the efficacy of EMF treatment for the prevention and treatment of OP. This may have resulted from the lack of a set of standard operating procedures in selecting EMF parameters for various studies, and the fact that EMFs have a strict window of bioactivity (Bagnato et al, 2016;Funk et al, 2009; C. Markos, 2005;Zhou et al, 2019Zhou et al, , 2011Zhou et al, , 2014S. Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cells were treated with LiCl as it induces cilia elongation in mice osteoblasts. ( 45 ) Notably, LiCl activates canonical Wnt signaling, a pathway previously implicated in cyst expansion of polycystic disease in animal models, through the inhibition of glycogen synthase kinase 3. ( 45 ) Following serum starvation, cells were treated with either 10mM or 25mM LiCl for 24 hours and processed for immunofluorescence analyses.…”
Section: Resultsmentioning
confidence: 99%
“…( 45 ) Notably, LiCl activates canonical Wnt signaling, a pathway previously implicated in cyst expansion of polycystic disease in animal models, through the inhibition of glycogen synthase kinase 3. ( 45 ) Following serum starvation, cells were treated with either 10mM or 25mM LiCl for 24 hours and processed for immunofluorescence analyses. Cilia length was measured using pericentrin to mark the cilium base acetylated α‐tubulin as microtubules extend to the tip of the organelle.…”
Section: Resultsmentioning
confidence: 99%
“…Then, GO analysis predicted that WNT5A regulated molecular functions including GTPase activity, biological processes such as signal translation, and biological pathways such as EGFR-dependent signaling events in glioma; differently, WNT10B regulated molecular functions including GTPase activity, biological processes such as signal translation, and biological pathways such as development biology in glioma. Finally, KEGG pathway analysis showed that WNT5A is primarily through the WNT/Ca+ pathway, also activates the canonical pathway [20,[48][49][50] and WNT10B has been only reported in the canonical WNT signaling pathway [51][52][53][54]. KEGG pathway analysis also showed that the neighbor genes of WNT5A were widely distributed in multiple pathways in the de novo pathways of glioma occurrence, in which crucial oncogenes (EGFR and MDM2) and 2 important tumor suppressors (PTEN and IKN4a/ARF) were closely correlated with WNT5A.…”
Section: Discussionmentioning
confidence: 99%